Réponses

2013-04-01T11:01:52+02:00

cosx = cox(pi/2 - x)  => x = + ou - (pi/2 - x) + k2pi

                                => x = pi/2 - x+ k2pi=>2x = pi/2 + k2pi => x = pi/4 + k2pi

                                => x = -pi/2 + x + k2pi => 0x = -pi/2+ k2pi impossible

 Sin ) = Sin (Pi/3-X)

(2X+(Pi/4) = (Pi/3-X) + k2pi => 2x + pi/4 = pi/3 - x + k2pi => 3x = pi/3 - pi/4 + k2pi

=> 3x = pi/12 + k2pi => x = pi/36 + k2pi/3 (3solutions)

ou bien

2x + pi/4 = pi - pi/3 + x + k2pi => x = 2pi/3 - pi/4 + k2pi => x = 5pi/12 + k2pi